ADAPTIVE MUTUAL CURRICULUM: A BREAKTHROUGH IN CHARACTER EDUCATION - Rohadi, Tedi (Pascasarjana IAIN Kudus, 2017)
Character education is perceived differently and has been implemented partially. In addition, its execution in classroom context seems to simply be on the concept level which later on leads to the ineffectiveness of the program. Therefore, a reference or guidance in the form of applicable curriculum is necessitated. The study seeks to create a model of an adaptive mutual curriculum that can provide a clear cut practical guidance for teachers in implementing character education and validates it. The mutual adaptive curriculum as the product of the study in its implementation is adjusted to contextual needs, real and existing condition, and adopted developmental requirements. The design and content of curriculum is designed and determined by the external contexts of teaching and learning. The adaptation is carried out in pre and whilst the process of the implementation. The design of mutual adaptive curriculum is actualized in the forms of objectives, content or materials, learning experiences, and evaluations which are realized in the form of curriculum manual and instructional materials and activities for students. Despite the weaknesses and the problems that the mutual adaptive curriculum has, it has in certain extent proven to be a validated model of curriculum in character education